2017
DOI: 10.5468/ogs.2017.60.2.200
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of loop electrosurgical excision procedure with cold coagulation for treating cervical intraepithelial neoplasia: A two center cohort study

Abstract: ObjectiveTo evaluate the efficacy of loop electrosurgical excision procedure (LEEP) combined with cold coagulation for treating cervical intraepithelial neoplasia (CIN).MethodsWe reviewed clinic-pathologic data of 498 patients treated with LEEP alone (n=354), and LEEP combined with cold coagulation (n=144) between January 2000 and December 2011. After LEEP, we followed up all patients by using Papanicolaou smear and human papillomavirus (HPV) test, and evaluated abnormal cervical cytology-free interval and hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…Positive cone margins are an important predictor for CIN persistence/recurrence after conization . A meta‐analysis confirmed that positive cone margins significantly increases the risk of persistence/recurrence.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…Positive cone margins are an important predictor for CIN persistence/recurrence after conization . A meta‐analysis confirmed that positive cone margins significantly increases the risk of persistence/recurrence.…”
Section: Discussionmentioning
confidence: 77%
“…In the treatment of HSIL, TCRC resulted not only in lower incidences of positive margins, persistence, and recurrence than did LEEP, but Positive cone margins are an important predictor for CIN persistence/recurrence after conization. [12][13][14] A meta-analysis 15 confirmed that positive cone margins significantly increases the risk of persistence/recurrence. In the present study, TCRC resulted in lower rates of both positive cone margins and persistence/recurrence than did LEEP.…”
Section: Discussionmentioning
confidence: 93%
“…Still, there is potential tendency among physicians to use Lugol's solutions for cases of high-grade CINs. Other authors have reported similarly high proportions of endocervical margin involvement in up to 60%–75% of cases with positive RMs 23,24 . Lugol's solution helps visualize the TZ of the uterine ectocervix and therefore seems to have no role in aiding lesion removal from the endocervix.…”
Section: Discussionmentioning
confidence: 95%
“…Other authors have reported similarly high proportions of endocervical margin involvement in up to 60%-75% of cases with positive RMs. 23,24 Lugol's solution helps visualize the TZ of the uterine ectocervix and therefore seems to have no role in aiding lesion removal from the endocervix. As women age, the TZ gradually migrates into the endocervical canal, explaining the relatively higher proportion of older patients with CIN who have positive RMs.…”
Section: Discussionmentioning
confidence: 99%
“…In the Lugol's solution group, up to twothirds of cases with positive resection margins showed involvement of the endocervix. Other authors have reported similarly high proportions of endocervical margin involvement in up to 60 ~ 75% of cases with positive resection margins [23,24]. Lugol's solution helps to visualize the TZ of the uterine ectocervix and, therefore, seems to have no role in aiding lesion removal from the endocervix.…”
Section: Discussionmentioning
confidence: 99%